'No‐one knows where you are': veterinary perceptions regarding safety and risk when alone and on‐call. (14th December 2019) - Irwin, Amy; Vikman, Janika; Ellis, Hannah
Abstract : Background: Veterinary work is considered high risk and involves working with a range of hazards, including large animals, high workload and long hours. A key potential hazard is making home visits and providing out‐of‐hours emergency care, where vets often work alone, without support and must travel long distances. The current study aimed to examine UK veterinary perceptions of safety culture, lone working and on‐call tasks to gain a deeper understanding of the risk and hazards involved. Methods: An online mixed‐methods survey was used to gather quantitative data relevant to practice safety culture and qualitative data regarding veterinary perception of lone working and on‐call work. A sample of 76 UK veterinarians were recruited. Results: The quantitative results suggest that there may be practice safety culture issues around a lack of communication and discussion pertaining to safety, particularly in terms of maintaining personal safety. Key themes within the qualitative data included the pressure to treat patients, potentially at personal risk, and feeling unsafe when meeting clients alone and in remote locations. Conclusion: These findings indicate that personal safety requires more attention and discussion within veterinary practices, and that safety protocols and requirements should be shared with clients.